Psychosocial development and ego identity of protagonists in selected works of Munro - Esfahani, Mehdi Hassanian (2010)
Del and Rose are two of the most discussed characters in the fiction of Alice Munro as they undergo series of (psychologically significant) incidents and make novellength stories. Since their publication, Lives of Girls and Women (1971) and The Beggar Maid: Stories of Flo and Rose (1978) are examined from different aspects,and are argued to be the representation of social changes, feminist waves, classbound and social stratification, cultural heritage and the like. In this dissertation, I try to depict the process of obtaining an ego identity by the protagonists and find an answer for the figurative ending of the stories. Ergo, I investigate psychological development and ego identity formation of the protagonists: examining chiefly stage five of Eriksonian theory of personality development i.e., ego identity vs. identity confusion, and includes partial characteristics of all other stages supposedly happen thoroughly during a lifespan. The protagonist’s process of identity development is mapped to interpret “Epilogue”, the ending, and suggest a plausible future for these characters. In addition, four identity statuses of James E. Marcia (from ‘being identity diffused’ to ‘achieving’ an ego identity) emphasizing the divergence of conferred personal identity and constructed ego identity, are discussed to differentiate the kinds of identity challenged and developed by under study characters during their lives. Mapping their process of psychosocial development and the struggles the protagonists undergo (including their dysfunctional relationships and their uneven life) leads to the interpretation of the story as a quest to resolve their identity crises. In addition, through Marcia’s concept of a foreclosed identity (which is an incomplete ego identity, needed to be re-examined) this study justifies the unique endings, in which dislike some cliché happy-ending plots, Del and Rose run away to begin a new future with no great promise of success.